y=4-3*4-3

Simple and best practice solution for y=4-3*4-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=4-3*4-3 equation:


Simplifying
y = 4 + -3 * 4 + -3

Multiply -3 * 4
y = 4 + -12 + -3

Combine like terms: 4 + -12 = -8
y = -8 + -3

Combine like terms: -8 + -3 = -11
y = -11

Solving
y = -11

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -11

See similar equations:

| 4x+11-4x=11 | | 7y-4=-2y+1+9y-5 | | 80.8=8(m+3.7) | | 13s+6p=332 | | 16/g=4 | | 5w-19=-6(w+5) | | 10x+12=8x+4 | | 4x-7=3x-12 | | 5m+5.75=43.25 | | 8x-(600+2.50x)=1200 | | w-1/3=2 | | -x+5=x-11 | | 3b=20 | | 3x+1y=5 | | 8=2(w-2) | | -6u+7= | | 5+d=8d-7 | | 3/5c=2c-7 | | 9-q=5 | | 24/48=50/x | | x+y=10000 | | 12k-11k+2=16 | | 12-8(4-s)+3(s+3)=27 | | 3-2(x-5)=13 | | x(3+2)+9=2x-12 | | 8w+2w-2=18 | | 5c+12-3c=28 | | x-sqrt(40-3x)=0 | | 4x+5(3x-3)=6 | | 2m-4=10+18 | | x(x-3)(x+12)=324 | | 3x+6y=-9 |

Equations solver categories